Silent Strike: Stroke in Context of Endocarditis – Brain Imaging as a Catalyst for Diagnosis - Stoican Iulia-Cosmina; Dragoș Dorin; Papagheorghe Atena; Guberna Suzana Maria; Tuta Sorin; Manea Maria Mirabela (Romanian Journal of Internal Medicine)
Endocarditis is a pathology which is rarely encountered in clinical practice that presents itself in various manners, thus posing a great challenge for the clinician in the process of formulating a timely diagnosis, especially given its potentially lethal evolution. The diagnosis of infective endocarditis is based on Modified Duke Criteria. A wide array of complications may accompany endocarditis, including septic or thrombotic emboli to various territories – those occluding branches of cerebral arteries result in ischemic strokes, which may be demonstrated by brain imaging and the symptoms which may range from mild mental status alteration to deep coma.